Pentingnya Upaya Pendidikan bagi Masyarakat Migran Perkotaan - H.M. Saleh Marzuki (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
Urbanization influences the structure of population and the life style of a group of population called urban migrants. There are interrelationships between urbanization and education. The migrants need educational services while (schooling) education motivates them to migrate to urban areas. Women and children need to be educated through the out-of-school programs. Values educa-tion should be implanted so that they will be aware that their new environments are different from their old ones. A Value Education Center needs to be established. A number of program can be organized to develop the indegenous, national and universal culture values through massmedia and vocational-skill training centers.